Impact of military conflicts on landscape transformation (a case study for the Aghdam district of the Republic of Azerbaijan) - Ismayilov, Mirnuh; Kuchinskaya, Irina; Karimova, Elina (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem statement: The Aghdam district of the Republic of Azerbaijan, under occupation for nearly 30 years, became an area of intensive degradation of both natural and anthropogenic landscapes. The scale of destruction caused by military and technological activities has led to significant ecological, social, and economic losses. The damage to natural and anthropogenic ecosystems is estimated to exceed 200 billion US dollars. More than 50 natural monuments were destroyed, and the infrastructure of 58 rural settlements and one city were devastated. Over 90,000 mines pose a constant threat and hinder the restoration of these areas.Objective: To conduct a landscape-oriented study aimed at assessing the consequences of military and technological activities, determining structural, genetic, and functional changes in the landscapes of the Aghdam district, and systematizing the transformed landscapes.Methods: Satellite imagery, field research data, and archival materials were applied during the research procedure. A systematic approach was applied for the analysis, classifying, and assessing the scale of transformation of natural and anthropogenic landscapes.Results: It was unraveled that the transformation of landscapes resulted from both direct and indirect impacts from military and technological activities. The classification of landscapes in the region revealed 2 main classes, 6 types, and 21 subtypes. The analysis identified a high degree of ecological degradation. Military actions exacerbated the degradation of natural components. Direct impacts included the destruction of forests, pastures, hydrological objects, and infrastructure, while indirect consequences have been experienced in the disturbance of natural balance and the deterioration of soil and water quality. An important aspect of the research is to identify functional changes in landscapes. The worsening environmental situation has led to a reduction in biodiversity, decreased water retention capacity, and an increased risk of soil erosion. In anthropogenic landscapes, there has been a complete loss of economic value in several areas, complicating the restoration process. The implemented classification provides the identification of major landscape groups based on the degree of transformation:Landscapes with minimal transformation (10% of the area), where changes are limited to local disturbances.Landscapes with moderate transformation (25%), are characterized by changes in vegetation structure and soil cover.Landscapes with high degrees of transformation (40%), where significant changes occur in ecosystems due to direct impacts.Landscapes with a complete loss of natural functions (25%), including areas that were destroyed by mines, infrastructure, and other military objects.Conclusion: The research systematized landscape changes and revealed the scale of the consequences of military conflicts. The presented results enable the application of a landscape-oriented approach to monitoring and restoring territories, including the development of reclamation, demining, and ecological function restoration measures. The proposed classification of transformed landscapes can serve as a foundation for future research and the development of sustainable land management strategies.